(untitled) (The International Journal for Scientific Research, 2025)
This study focuses on analyzing AI-powered digital campaigns in Saudi Arabia, specifically in terms of public reliance on and interaction with these campaigns across various digital platforms. The researcher employed a questionnaire as the primary data collection tool, targeting an active sample of social media users. The data was analyzed using SPSS software. Findings revealed that Facebook, Snapchat, and TikTok are the most commonly used platforms for engaging with such campaigns, with 32% of respondents encountering them daily. Despite this high level of exposure, more than half of the sample expressed dissatisfaction with the accuracy of content targeting based on their interests. Additionally, "purchasing" emerged as the most prominent form of engagement, driven by factors such as content alignment with personal preferences, relatable language, exclusive offers, and appealing design. The study recommends enhancing AI algorithms to improve targeting precision, focusing efforts on the most popular platforms, and delivering engaging and well-targeted marketing content. Furthermore, it emphasizes the importance of incorporating behavioral incentives to increase the actual impact on audiences.